Feasibility and age-related trends of a home-based online exercise program in adolescents with idiopathic scoliosis - Wang, Jing; Su, Youcun (Frontiers in Pediatrics, 2025)
BackgroundIdiopathic scoliosis (IS) is a three-dimensional spinal deformity that often progresses during adolescence. While bracing and exercise therapies are standard conservative treatments, limited research has examined the feasibility of fully online, home-based combined exercise programs and the clinical trends observed during participation —especially in adolescents undergoing brace treatment. This single-arm prospective cohort study (without a control group) aimed to evaluate the feasibility of a six-month, fully online, home-based Schroth-Pilates program combined with brace treatment in adolescents with IS, and to observe potential age-related trends in clinical measures and adherence.MethodsA single-center prospective cohort design was used involving 114 adolescents with IS (Cobb angle 10°–45°) receiving standard brace treatment. Participants engaged in supervised online Schroth-Pilates sessions three times per week for six months. Primary measures included Cobb angle and ATR, recorded at baseline and post-program. Feasibility was assessed via program completion and adherence rates. Mixed-design ANOVAs were used to explore trends over time and between age groups (10–13 vs. 14–17 years).ResultsThe overall program completion rate was 97.4%, with no significant adherence differences between age groups. Significant improvements were observed in Cobb angle [F(1,112) = 16.42, p < .001, η2 = .255] and ATR [F(1,112) = 11.87, p = .001, η2 = .198], both exceeding the minimum clinically important difference for adolescents with IS. Higher adherence was positively correlated with greater reductions in Cobb angle and ATR, suggesting that consistent participation enhanced treatment outcomes. Younger participants demonstrated greater mean improvements, possibly reflecting higher flexibility and growth potential.ConclusionA fully online, home-based Schroth–Pilates program is feasible and clinically effective for adolescents with IS, achieving high adherence and meaningful improvements in spinal curvature and trunk rotation—particularly among younger participants. These results support the clinical viability of virtual scoliosis rehabilitation and highlight the need for future controlled and longitudinal studies to confirm long-term outcomes.